Urban metabolism: a dual-perspective case study and its implications in the urban political economy of developing nations for an effective SDG framework - Zorba, R.; Malarvizhi, Ganapathi (Frontiers in Sustainable Cities, 2025)
Urban Metabolism is derived from a biological-based mechanism wherein a city is metaphorically analyzed from a biological perspective, which tracks the transformation of resources and addresses key questions related to self-sufficiency and consumer behavior. This research, for the first time, explores Urban Metabolism as a tool to evaluate sustainability-related framework and standards for urban regions on both global and local scales to address regional disparity and better means to devolve powers to local planning institutions. In the first half of the study, an adaptive approach was used to categorize the concept and find its connection with SDGs, wherein it was inferred that a new section under economic ecology has evolved, which requires policy interventions as its application at regional context creates lacunae in terms of UPE (Urban Political Economy). Furthermore, the study explores case studies and identifies the characteristics of urban metabolic systems to comprehend the trend in the idea and the necessity of using the UM lens at two different scales with two different narratives to solve entirely different challenges under the same component. The second part of the article looks at how the concept is used within current research. The results of the “perspective methods” were compared to gathered standard guidelines, and their shortcomings were noted to help close the implementation gap between researchers and practitioners. This suggests that policies, frameworks, guidelines, and other documents should adopt the discussed integrated approach to devolve power to local planning areas.